Conserved Pbp1/Ataxin-2 regulates retrotransposon activity and connects polyglutamine expansion-driven protein aggregation to lifespan-controlling rDNA repeats. (December 2018) - Ostrowski, Lauren; Hall, Amanda; Szafranski, Kirk; Oshidari, Roxanne; Abraham, Karan; Chan, Janet; Krustev, Christian; Zhang, Kevin; Wang, Ashley; Liu, Yupeng; Guo, Ru; Mekhail, Karim
Abstract Ribosomal DNA (rDNA) repeat instability and protein aggregation are thought to be two major and independent drivers of cellular aging. Pbp1, the yeast ortholog of human ATXN2, maintains rDNA repeat stability and lifespan via suppression of RNA–DNA hybrids. ATXN2 polyglutamine expansion drives neurodegeneration causing spinocerebellar ataxia type 2 and promoting amyotrophic lateral sclerosis. Here, molecular characterization of Pbp1 revealed that its knockout or subjection to disease-modeling polyQ expansion represses Ty1 (Transposons of Yeast) retrotransposons by respectively promoting Trf4-depedendent RNA turnover and Ty1 Gag protein aggregation. This aggregation, but not its impact on retrotransposition, compromises rDNA repeat stability and shortens lifespan by hyper-activating Trf4-dependent turnover of intergenic ncRNA within the repeats. We uncover a function for the conserved Pbp1/ATXN2 proteins in the promotion of retrotransposition, create and describe powerful yeast genetic models of ATXN2-linked neurodegenerative diseases, and connect the major aging mechanisms of rDNA instability and protein aggregation. Lauren Ostrowski, Amanda Hall et al. report a molecular characterization of Pbp1, the yeast ortholog of the neurodegenerative disease-associated human ATXN2. They find thatPbp1 knockout or polyQ expansion compromises rDNA repeat stability via a mechanism linking neurodegenerative protein aggregation and aging.